Citrus Irrigation With Desalinated Seawater Under a Climate Change Scenario - Navarro, Josefa María; Antolinos, Vera; Robles, Juan Miguel; Botía, Pablo (Frontiers in Plant Science, 2022)
In arid and semiarid regions, the current lack of natural water resources is driving the use of alternative sources for crop irrigation, such as desalinated seawater (DSW). However, the use of DSW could affect crop productivity due to its chemical composition (predominance of phytotoxic ions: Na+, Cl−, and B). Citrus species are classified as salt and boron-sensitive; however, the rootstock plays a fundamental role in the tree's tolerance of abiotic stresses. One-year-old ‘Verna’ lemon trees grafted on two rootstocks (Citrus macrophylla, CM, and sour orange, SO) were used. These rootstocks differ in their salinity and boron tolerance, SO being more tolerant than CM. The experiment was carried out at high temperature (35/27ºC) and the plants were irrigated with three types of water supplemented with Hoagland nutrients: DSW, DLB (DSW with low boron,), and Control (distilled water). The plants were irrigated three times per week and harvested seven months after the treatments started. The response to high levels of Cl-, Na+, and B was rootstock-dependent. Under the high temperature conditions, the growth of plants grafted on SO was not affected by DSW, and these plants did not reach the Cl- threshold of phytotoxicity, so the decrease in the shoot growth of plants grafted on CM due to DSW irrigation was related more to Cl- rather than the foliar Na+ accumulation. Plants grafted on SO and irrigated with DSW accumulated more B than those grafted on CM, surpassing the threshold of phytotoxicity and producing greater oxidative stress. As the growth of these plants was not reduced, the effects of DSW on plant growth were not directly related to the concentration of B and there must be some mechanisms that allow these plants to withstand the negative effects of high foliar B, such as the increased levels of quaternary ammonium compounds. Since the response of citrus plants to DSW depended on the rootstock, the results obtained in this experiment, using DSW at high temperature, could be useful for the future management of citrus crops, because climate change will increase temperatures and exacerbate the scarcity of water resources in citrus-growing areas.